THE ASSESSMENT OF EMPLOYEE ENGAGEMENT LEVEL FOR THE IMPLEMENTATION OF NEW WAYS OF WORKING (CASE STUDY: PT ISAT â INMARSAT INDONESIA) - Xaverius Budiyono, Fransiskus
The employee engagement is one key success to make employee working as best as they can, and it must be built to create great working condition. High level engagement from employee can make more revenue and profit because the employees will work hard for themselves and for their company. Inmarsat employees are in transition period for the ways of working and it is the adaptation from the covid-19 pandemic and the introduction of the digital transformation.